2004
DOI: 10.1007/s11177-005-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence of mykizha (Parasalmo (Oncorhynchus) mykiss) from Kamchatka inferred from restriction analysis and sequencing of mtDNA cytochrome b gene

Abstract: The populations of mykizha Parasalmo (O.) mykiss from western and eastern coasts of Kamchatka were studied by restriction analysis of a fragment of fish mitochondrial genome that included the control region and the region of the cytochrome b gene ( cytb ). The restriction patterns obtained with five enzymes ( Msp I; Tru 1I; Rsa I; Bsu RI; Dde I) were identical in all studied individuals. Sequencing of the cytb gene showed high similarity between all samples (99.6-100%). In general, the geographical group of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previous studies have reported reduced allozyme and mitochondrial DNA variability in Kamchatkan populations (the north-western edge of the species' range) compared with North America (Osinov & Pavlov 1994;Pavlov 2000;Pavlov et al 2004). We also found evidence for reduced microsatellite diversity in populations from Kamchatka.…”
Section: Comparability Of Kamchatka and Eastern Pacific O Mykiss Popmentioning
confidence: 97%
“…Previous studies have reported reduced allozyme and mitochondrial DNA variability in Kamchatkan populations (the north-western edge of the species' range) compared with North America (Osinov & Pavlov 1994;Pavlov 2000;Pavlov et al 2004). We also found evidence for reduced microsatellite diversity in populations from Kamchatka.…”
Section: Comparability Of Kamchatka and Eastern Pacific O Mykiss Popmentioning
confidence: 97%
“…This makes salmon a unique object for studying the problems of the origin, formation of the wild type population structure, mechanisms of microevolution, and speciation pro cesses. An important feature of the Kamchatka group of mykiss populations is the depletion of the genome in the Asian part of the range [1] and a small number of effective population genetic markers. The phyloge netic subdivision of the Kamchatka mykiss popula tions was studied insufficiently and primarily by our group of authors.…”
mentioning
confidence: 99%